Bubble flow simulations using the intersection marker (ISM) interface tracking method. Issue 1 (2nd January 2018) - Ho, Mark; Yeoh, Guan Heng; Reizes, John Arthur; Timchenko, Victoria
Abstract : Purpose: Interface distinct two-phase computational fluid dynamics (CFD) simulations require accurate tracking in surface curvature, surface area and volume fraction data to precisely calculate effects such as surface tension, interphase momentum and interphase heat and mass transfer exchanges. To attain a higher level of accuracy in two-phase flow CFD simulations, the intersection marker (ISM) method was developed. The ISM method has cell-by-cell remeshing capability that is volume conservative, maintains surface continuity and is suited for the tracking of interface deformation in transient two-phase flow simulations. Studies of isothermal single bubbles rising in quiescent water were carried out to test the ISM method for two-phase flow simulations. Design/methodology/approach: The ISM method is a hybrid Lagrangian–Eulerian front tracking algorithm which can model an arbitrary three-dimensional surface within an array of cubic control volumes. Fortran95 was used to implement the ISM method, which resulted in approximately 25, 000+ lines of written code and comments. To demonstrate the feasibility of the ISM algorithm for two-phase flow simulations, the ISM algorithm was coupled with an in-house CFD code, which was modified to simulate two-phase flows using a single fluid formulation. The constitutional equations incorporated terms of variable density and viscosity. In addition, body force source terms were included in the momentum equation to account for surface tension and buoyancy effects. Findings: The performance of two-phase flow simulations was benchmarked against experimental data for four air/water bubbles with 1, 2.5, 5 and 10 mm of diameter rising in quiescent fluid. A variety of bubble sizes were tested to demonstrate the accuracy of the ISM interface tracking method. The results attained were in close agreement with experimental observations. Practical implications: The results obtained show that the ISM method is a viable means for interface tracking of two-phase flow CFD simulations. Other applications of the ISM method include simulations of solid–fluid interaction and other immersed boundary flow problems. Originality/value: The ISM method is a novel approach to front tracking, and the results shown are original in content.